Building the Child Safety Collaborative Innovation and Improvement Network: How does it work and what is it achieving?. (16th February 2018) - Leonardo, Jennifer B; Spicer, Rebecca S; Katradis, Maria; Allison, Jennifer; Thomas, Rebekah
Abstract : Objective: This study investigated whether the Child Safety Collaborative Innovation and Improvement Network (CS CoIIN) framework could be applied in the field of injury and violence prevention to reduce fatalities, hospitalizations and emergency department visits among 0–19 year olds. Sample: Twenty-one states/jurisdictions were accepted into cohort 1 of the CS CoIIN, and 14 were engaged from March 2016 through April 2017. A quality improvement framework was used to test, implement and spread evidence-based change ideas (strategies and programs) in child passenger safety, falls prevention, interpersonal violence prevention, suicide and self-harm prevention and teen driver safety. Procedures: Outcome and process measure data were analyzed using run chart rules. Descriptive data were analyzed for participation measures and descriptive statistics were produced. Qualitative data were analyzed to identify key themes. Results: Seventy-six percent of CS CoIIN states/jurisdictions were engaged in activities and used data to inform decision making. Within a year, states/jurisdictions were able to test and implement evidence-based change ideas in pilot sites. A small group showed improvement in process measures and were ready to spread change ideas. Improvement in outcome measures was not achieved; however, 25% of states/jurisdictions identified data sources and reported on real-time outcome measures. Conclusions: Evidence indicates the CS CoIIN framework can be applied to make progress on process measures, but more time is needed to determine if this will result in progress on long-term outcome measures of fatalities, hospitalizations and emergency department visits. Seventeen states/jurisdictions will participate in cohort 2.